Time biases: exploring the work–life balance of single Nigerian managers and professionals. Issue 2 (26th February 2020) - Akanji, Babatunde; Mordi, Chima; Simpson, Ruth; Adisa, Toyin Ajibade; Oruh, Emeka Smart
Abstract : Purpose: This study investigates the overarching ideology of work–life balance (WLB) or conflict as predominantly being a work–family affair. Based on a Nigerian study, and using organisational justice as a theoretical lens, it explores perceived fairness in accessing family-friendly policies by managers and professionals who are single and do not have children – a workgroup conventionally ignored in research on WLB. Design/methodology/approach: Relying on an interpretivist approach, the data set comprises of interviews with 24 bank managers and 20 medical doctors working in Nigeria. Findings: The authors' findings highlight employers' misconceptions concerning the non-work preferences and commitments of singles as well as an undervaluation by employers of their non-work time. Conceptualised as "time biases", such time is routinely invaded by the organisation, with profound implications for perceptions of fairness. This fosters backlash behaviours with potential detrimental effects in terms of organisational effectiveness. Research limitations/implications: The study is limited to investigating the WLB of singles in high-status roles, namely banking and medical careers. Future research may examine the experiences of a more diverse range of occupations. The sample comprises heterosexual, never-married professionals, whose experiences may differ from other categories of single workers, such as childless divorced people, widows, non-heterosexual singles and partners who have no children. Practical implications: In order to avoid counterproductive behaviours in the workplace, WLB policies should not only focus on those with childcare concerns. Inclusive work–life policies for other household structures, such as single-persons, are necessary for improving overall organisational well-being. Originality/value: The majority of WLB studies have been undertaken in Western and Asian contexts, to the neglect of the Sub-Saharan African experience. Additionally, research tends to focus on WLB issues on the part of working parents, overlooking the difficulties faced by singles.